Sexual Risk Behaviors Constructed in Iranian Women’s Life with Substance Use Disorders: A New Implication of Human Ecological Theory - Mansoureh Jamshidimanesh; Seyed Abbas Mousavi; Effat Merghati-Khoei; Mohammad Hassan Emamian; Afsaneh Keramat (Addiction and Health, 2016)
Background: Drug abuse is one of the important variables influencing protective sexual behavior. The objective of this study was to explore how risky sexual behaviors develop in drug abusing women using human ecological theory.Methods: In this study, we used a descriptive exploratory approach. The participants were 32 drug abusing women from two of the selected drop-in centers (DICs) in south Tehran, Iran, where we could have access to a vast number of female drug users. Data was collected using semi-structured face-to-face interviews. Qualitative content analysis was used to analyze the data using Graneheim and Lundman procedure.Findings: Risky sexual behavior in drug use disorders in women was found in four themes with thirteen emerged; sexual untaught at micro-system with two subthemes “unsafe home” and “drop out of school”, Perception of differences at meso-system with three subthemes “lack of link between family and school”, “doing manly behavior” and “low awareness of health puberty than peers”, inappropriate marriages at exo-system with three subthemes “stigma”, “fear of losing love relationship” and “self-devotion”, marginalization at macro-system with four subthemes “barrier access to rights”, “selling sex as a tool of security”, “lack of belief as a sex worker” and “mistrust and doubt partner” using implication of human ecological theory.Conclusion: Findings suggest that strategies supporting the discovery of risky sexual behaviors in drug use disorders in women are important in order to provide counseling and education to form their decisions toward safety sex.